Pyromellitic diimide containing four-member heterocyclic derivatives synthesis, characterization and evaluation antimicrobial activity - Zahraa H.H. Al-Hamidawi,; Suaad M.H. Al-Majidi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
In this study, pyromellitic diimide and sodium hydroxide were reacted in dry DMF to yield a sodium salt pyromellitic diimide, which was then combined with ethylchloro acetate to generate N, N´-bis (ethyl acetate). This process was used to synthesize new four-member heterocyclic derivatives, 1,3diazetidene. By chemically mixing substance (1) with hydrazine hydrate, pyromethyl dichloride produces the corresponding hydrazine derivatives (2). Compound (2) underwent a condensation reaction with a range of para-aromatic aldehydes, yielding Schiff base derivatives (3–7). These Schiff base derivatives were then cyclized using phenyl isocyanate, P-Chloro phenylisocyante, and phenyl isothiocyanate to produce four-member heterocyclic derivatives (8–22). The produced compounds' physicochemical characteristics and melting points were identified. To identify novel compounds, spectral approaches such as 1H-NMR, 13C-NMR, and FT-IR were employed. Furthermore, tests were conducted on the biological activity components.